Antiviral Activity of Repurposing Ivermectin against a Panel of 30 Clinical SARS-CoV-2 Strains Belonging to 14 Variants - Océane Delandre; Mathieu Gendrot; Priscilla Jardot; Marion Le Bideau; Manon Boxberger; Céline Boschi; Isabelle Fonta; Joel Mosnier; Sébastien Hutter; Anthony Levasseur; Bernard La Scola; Bruno Pradines (MDPI AG, 2022)
Over the past two years, several variants of SARS-CoV-2 have emerged and spread all over the world. However, infectivity, clinical severity, re-infection, virulence, transmissibility, vaccine responses and escape, and epidemiological aspects have differed between SARS-CoV-2 variants. Currently, very few treatments are recommended against SARS-CoV-2. Identification of effective drugs among repurposing FDA-approved drugs is a rapid, efficient and low-cost strategy against SARS-CoV-2. One of those drugs is ivermectin. Ivermectin is an antihelminthic agent that previously showed in vitro effects against a SARS-CoV-2 isolate (Australia/VI01/2020 isolate) with an IC50 of around 2 µM. We evaluated the in vitro activity of ivermectin on Vero E6 cells infected with 30 clinically isolated SARS-CoV-2 strains belonging to 14 different variants, and particularly 17 strains belonging to six variants of concern (VOC) (variants related to Wuhan, alpha, beta, gamma, delta and omicron). The in vitro activity of ivermectin was compared to those of chloroquine and remdesivir. Unlike chloroquine (EC50 from 4.3 ± 2.5 to 29.3 ± 5.2 µM) or remdesivir (EC50 from 0.4 ± 0.3 to 25.2 ± 9.4 µM), ivermectin showed a relatively homogeneous in vitro activity against SARS-CoV-2 regardless of the strains or variants (EC50 from 5.1 ± 0.5 to 6.7 ± 0.4 µM), except for one omicron strain (EC50 = 1.3 ± 0.5 µM). Ivermectin (No. EC50 = 219, mean EC50 = 5.7 ± 1.0 µM) was, overall, more potent in vitro than chloroquine (No. EC50 = 214, mean EC50 = 16.1 ± 9.0 µM) (p = 1.3 × 10−34) and remdesivir (No. EC50 = 201, mean EC50 = 11.9 ± 10.0 µM) (p = 1.6 × 10−13). These results should be interpreted with caution regarding the potential use of ivermectin in SARS-CoV-2-infected patients: it is difficult to translate in vitro study results into actual clinical treatment in patients.